Penerapan Model Pembelajaran Problem Based Learning dalam Upaya Meningkatkan Pemahaman Konsep dan Minat Belajar Matematika Siswa Kelas XI IPS di SMAN 1 Sambelia - Dian Tina Safitri; Ahmad Muzaki; Ade Kurniawan (Jurnal Kependidikan Ki Hajar Dewantara, 2024)
This research aims to describe the implementation of the problem-based learning model in an effort to improve conceptual understanding and student interest in learning among XI IPA 1 students at SMAN 1 Sambelia. This study is a classroom action research (CAR) based on the Kemmis & Mc. Taggart model, conducted in two cycles, involving 19 out of 30 students as subjects. Each cycle consists of three meetings; the first two meetings involve learning activities, while the third meeting involves evaluation. The data generated in this study includes qualitative data, specifically the results of student interest questionnaires in learning mathematics, and quantitative data, specifically the evaluation scores for students' conceptual understanding of mathematics. The implementation of the problem-based learning model on the topic of derivatives in XI IPS 1 class showed an increase in students' conceptual understanding and interest in learning mathematics. The results indicate an improvement from cycle I to cycle II, where the evaluation test scores for students' conceptual understanding in cycle I were 61.1, increasing to 76.1 in cycle II. Furthermore, the average student interest in learning in cycle I was 72%, categorized as high, which increased to 84%, categorized as very high, in cycle II. Thus, the application of the problem-based learning model in the mathematics subject on the topic of derivatives can enhance the conceptual understanding and interest in learning mathematics among XI IPS 1 students at SMAN 1 Sambelia